E-Finance Information Technology Governance Analysis Using the Domain MEA COBIT 5 Frameworks in the Regional Financial Agency of Salatiga City - Delvy Alva Pattiasina; Yani Rahardja; Melkior N.N Sitokdana (Politeknik Pertanian Negeri Samarinda, 2020)
Utilization of Information Technology (IT) is able to produce good government management. The implementation of E-Finance continues to be developed by the Regional Finance Agency